2010
DOI: 10.1021/om100251j
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Polymerization Characteristics of an Electron-Deficient Nickel(II) Phenoxyiminato Catalyst Modulated by Non-Innocent Intramolecular Hydrogen Bonding

Abstract: The synthesis and characterization of the neutrally charged electron-deficient nickel(II) phenoxyiminato catalyst {2-(hydroxydiphenylmethyl)-4-tert-butyl-[6-(2,6-diisopropylphenyl)]salicylaldiminato}-methyl(trimethylphosphine)nickel(II) (1b) with an intramolecular hydrogen bond directed toward the active catalytic site is reported. At room temperature, catalyst 1b exhibits 2.5Â greater ethylene polymerization activity and 2Â greater polyethylene product branching than an analogous catalyst without the hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 91 publications
1
35
0
Order By: Relevance
“…Microstructural analysis of the polyethylenes produced by (CF 3 )FI 2 ‐Ni(OH) indicates lower M w polyethylene with similar branch numbers versus the polyethylenes produced by (CF 3 )FI 2 ‐Ni 2 . In previous work, the effects of installing an intramolecular hydrogen bond directed toward a polymerization‐active Ni II center were investigated,14c and it was concluded that installing the hydrogen bond adjacent to the Ni center leads to a more electron‐deficient catalyst as shown below; see also ref. 14c), increasing ethylene polymerization activity and depressing product polyethylene M w .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microstructural analysis of the polyethylenes produced by (CF 3 )FI 2 ‐Ni(OH) indicates lower M w polyethylene with similar branch numbers versus the polyethylenes produced by (CF 3 )FI 2 ‐Ni 2 . In previous work, the effects of installing an intramolecular hydrogen bond directed toward a polymerization‐active Ni II center were investigated,14c and it was concluded that installing the hydrogen bond adjacent to the Ni center leads to a more electron‐deficient catalyst as shown below; see also ref. 14c), increasing ethylene polymerization activity and depressing product polyethylene M w .…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, the effects of installing an intramolecular hydrogen bond directed toward a polymerization‐active Ni II center were investigated,14c and it was concluded that installing the hydrogen bond adjacent to the Ni center leads to a more electron‐deficient catalyst as shown below; see also ref. 14c), increasing ethylene polymerization activity and depressing product polyethylene M w . Similar conclusions can be drawn here when the polymerization results for (CF 3 )FI 2 ‐N i(OH) and (CF 3 )FI 2 ‐N i 2 are compared.…”
Section: Discussionmentioning
confidence: 99%
“…This means the approximate [eth] of 1 m is an underestimation and b is therefore somewhat overestimated, but still small enough to meet the experimental requirement. The lower molecular weights observed from polymerizations in the absence of phosphine but in the presence of coordinating solvents (for example, tetrahydrofuran, di-A C H T U N G T R E N N U N G methyl ether, and acetone) or additives (for example, ethyl oleate, pyridine, and tetrahydrothiophene) [56,72,111] naturally lead to speculation that these molecules may play a role similar to phosphine in the termination pathway described in Scheme 4. However, this aspect is outside the scope of this paper but could be an interesting subject for a future study.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Thus, the presence of bulky substituents in the backbone of the salicylamidinato ligand is a key requirement to generate highly active nickel catalysts for olefin polymerization. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] On the other hand, the use of less sterically encumbered phenoxy-imine ligands afforded predominantly nickel catalysts for ethylene oligomerization. [72][73][74][75][76] Selected examples are presented in Chart 1.…”
Section: Introductionmentioning
confidence: 99%